A Comprehensive Review on Level 2 Charging System for Electric Vehicles. Issue 3 (3rd July 2018) - Khan, Saadullah; Shariff, Samir; Ahmad, Aqueel; Saad Alam, Mohammad
Abstract: The commercialized deployment and fast adoption of electrified transportation system, i.e. electric vehicles (EVs) and plug-in hybrid-electric vehicles (PHEVs) necessitate the fast, reliable and economical electric vehicle supply equipment (EVSE) infrastructure (i.e. EV chargers). As a matter of fact, EVs are the best supplement of ICEVs due to their energy efficient and environmentally friendly nature. But their wide adoption has checked by the insufficient charging infrastructure in the world. The work presented in this paper provides state of the art review of Level 2 charging technologies for EVs and their sustainable deployment, characteristics, and standards available in the open literature, as well as sustainable smart grid interaction and potential safety measures. The manuscript also forecasts comprehensively a coherent view of the current status, economic assessment, power market operation and control and safety aspects of EVSE to assess the marketable viability of Level 2 charging system. The work will be extremely useful to researchers in this field, industry personals, and investment representatives and groups as a ready reference of the charging system of EVs, with information on significant characteristics and standards of xEV charging system. Abstract :